2015
DOI: 10.1007/s00267-015-0470-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Microbial Community Structure and Soil Biological Properties in Mined Dune Areas During Re-vegetation

Abstract: The aim of this study was to describe the impact of re-vegetation on the restoration of microbial community structure and soil microbiological properties in sand dunes that had been affected by mining activity. Soil samples were collected during the dry and rainy seasons from a chronosequence (1, 9, 21 years) of re-vegetated dunes using a single preserved dune as a reference. The composition of the fatty acid methyl esters and soil microbial properties were evaluated. The results showed that the changes in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Although both bacteria and fungi biomass increased with plant diversity, fungi:bacteria ratio was higher in plant mixtures than in monocultures, suggesting that fungi may benefit more from plant species mixture, likely because fungi, but not bacteria, can transfer nutrients from high- to low-nutrient plant litter when plant mixtures include species with different nutrient contents 143 , 144 . Also, G+:G− bacteria ratio decreased in mixtures, attributable to increased soil moisture with plant diversity 22 , which promotes the relative abundance of G− bacteria 23 , 24 . In contrast to our hypothesis, we did not find an effect of plant mixtures on microbial C:N. This is likely because plant diversity increases soil carbon and simultaneously increases nitrogen retention 145 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both bacteria and fungi biomass increased with plant diversity, fungi:bacteria ratio was higher in plant mixtures than in monocultures, suggesting that fungi may benefit more from plant species mixture, likely because fungi, but not bacteria, can transfer nutrients from high- to low-nutrient plant litter when plant mixtures include species with different nutrient contents 143 , 144 . Also, G+:G− bacteria ratio decreased in mixtures, attributable to increased soil moisture with plant diversity 22 , which promotes the relative abundance of G− bacteria 23 , 24 . In contrast to our hypothesis, we did not find an effect of plant mixtures on microbial C:N. This is likely because plant diversity increases soil carbon and simultaneously increases nitrogen retention 145 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, plant species diversity increases soil moisture by higher leaf area index 22 . As G+ bacteria are more dominant than G− bacteria in dry conditions due to their thicker cell walls and capacity to form spores 23 , 24 , the reduced soil moisture associated with lower plant diversity may increase G+:G− bacteria ratio. Therefore, our first hypothesis is that plant diversity would increase the total microbial biomass, bacterial and fungal biomass, and fungi:bacteria ratio, but decrease G+:G− bacteria ratio due to plant diversity induced increases of carbon inputs and soil moisture 14 , 17 , 18 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Mining is an essential human activity; however, it is an activity with a considerable impact on the landscape and on ecosystems, leading to the need for rehabilitation processes in the mined areas, especially through the use of revegetation to recompose, protect, and improve soil conditions (Escobar et al, ; Quadros et al, ; Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Changes caused by mining influence the diversity and density of soil organisms, affecting biochemical processes that are essential for sustainability of the ecosystems (Borges et al, 2016;Escobar et al, 2015;Silva et al, 2018). Among these processes, we emphasize biological nitrogen fixation (BNF), carried out by symbiotic and associative diazotrophic bacteria, which is extremely important for the ecosystems by making nitrogen available in a form that can be assimilated by plants, which promotes greater plant development.…”
mentioning
confidence: 99%
“…However, after revegetation restoration, tailing sand could be quickly covered by plants that could reduce the evaporation of soil water and could regulate the soil temperature and moisture (Berndtsson et al, 1996;Mukhopadhyay et al, 2016;Zhao et al, 2016). The soil quality could then be gradually modified (Zhang et al, 2014) and could promote the better growth of plants (Li et al, 2016), while the activities of soil microbes and soil fauna are also enhanced (Cristescu et al, 2012;Escobar et al, 2015;Nelson et al, 2015;Xie et al, 2015), which directly results in changes in the structure of the soil fauna (Topp et al, 2001;Yang and Gao, 2001;Cristescu et al, 2012). In the present study, significant differences were observed in the community structure of the soil fauna among the four revegetation patterns in the Dexing Copper Mine tailings pools, which indicated that communities of the soil fauna could be influenced significantly by the ecological restoration by revegetation (Cristescu et al, 2012).…”
Section: The Structure Of the Soil Fauna Community In Different Revegmentioning
confidence: 99%